2021
DOI: 10.3390/ijms22158145
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Microbiota Metabolites in Preterm Birth: Pathological and Therapeutic Insights

Abstract: Preterm birth (PTB) refers to the birth of infants before 37 weeks of gestation and is a challenging issue worldwide. Evidence reveals that PTB is a multifactorial dysregulation mediated by a complex molecular mechanism. Thus, a better understanding of the complex molecular mechanisms underlying PTB is a prerequisite to explore effective therapeutic approaches. During early pregnancy, various physiological and metabolic changes occur as a result of endocrine and immune metabolism. The microbiota controls the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 168 publications
0
16
1
Order By: Relevance
“…Nevertheless, probiotics are expected to play a significant role in maintaining gestational health. 25,26 The major strength of the present study is that it was the first to demonstrate the preventative effects of probiotics against recurrent sPTD. The limitations of the present study are as follows: (1) the management strategies for patients with preterm labor, cervical insufficiency, and pPROM differed among the seven participating hospitals.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, probiotics are expected to play a significant role in maintaining gestational health. 25,26 The major strength of the present study is that it was the first to demonstrate the preventative effects of probiotics against recurrent sPTD. The limitations of the present study are as follows: (1) the management strategies for patients with preterm labor, cervical insufficiency, and pPROM differed among the seven participating hospitals.…”
Section: Discussionmentioning
confidence: 93%
“…Gravida and Para was significantly larger in the probiotics group (3 [1][2][3][4][5][6], and 2 [1][2][3][4]) than in the nonprobiotics group (2 [1-10], and 1 [1][2][3][4][5][6]; p < 0.001, and p = 0.007). The delivery weeks of sPTD in past pregnancy history was significantly shorter in the probiotics group (27 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]) than in the nonprobiotics group (35 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]; p < 0.001). Data on 255 pregnant women who did not take probiotics were obtained from six hospitals as the nonprobiotics group for comparisons of the preventative effects of probiotics against recurrent spontaneous preterm delivery…”
Section: Resultsmentioning
confidence: 99%
“…It means that, even in term babies, both physical and emotional development is required to progress toward maturity. This complex process is even more complicated in preterm babies (Haumont et al, 2012;Ansari et al, 2021). Although premature baby's development happens in the same order as it would have happened in the womb, premature infants develop differently than full-term babies, as they are exposed to a different environment during this development and do not count with the same environmental support.…”
Section: Discussionmentioning
confidence: 99%
“…Premature delivery can be considered as a syndrome with many causes and factors (Haumont et al, 2012;Ansari et al, 2021). Medical conditions (urinary tract or vaginal infections, chorioamnionitis, uterine or cervical abnormalities, high blood pressure or obesity), lifestyle factors (high stress levels and long working hours, no prenatal care or drug use) or demographic factors (ethnicity, delayed fertility, multiple birth rate by assisted fertility with advanced maternal age), among others, can affect the birth outcome (Haumont et al, 2012;Ansari et al, 2021). A recent study has shown that pathways related to the oxidative stress response and the inflammation are deregulated in the placenta of spontaneous preterm deliveries (Lien et al, 2021), indicating the presence of an altered fetal environment for these babies.…”
mentioning
confidence: 99%
“…In healthy pregnancies, the colonization of the microbiota of the intrauterine cavity originates exclusively in the ascending pathway through the urogenital tract (urinary, cervical, and vaginal) and the hematogenous route through the placenta after translocation from the digestive tract (oral and intestinal). The oral and intestinal microbiota stability is affected by extrinsic factors, especially diet, which influence the dynamics of the cervicovaginal microbiota [ 45 , 46 ].…”
Section: Maternal Fetal and Neonatal Microbiotamentioning
confidence: 99%